Review of Primary and Secondary Education Institutions Scholarship Exam Science Questions According to the Renewed Bloom Taxonomy - Osman Doğan; Cezmi Ünal (Uluslararası Türk Eğitim Bilimleri Dergisi)
In this research, secondary school science questions in the Primary and Secondary Education Institutions Scholarship Examination (IOKBS) were examined. IOKBS science questions from 2018 to 2023 (6 years) constitute the sample of the research. While examining the questions, evaluations were made according to the renewed Bloom taxonomy (RBT) criteria. Qualitative research, which is based on understanding and questioning an event in depth, constitutes the research method of the study. Document analysis, which is a qualitative research method and allows access to written sources without wasting time, was used to collect data. In total, 600 science questions in IOKBS were analyzed. The questions were categorized according to knowledge and cognitive process dimensions of RBT, and their frequencies were calculated. When 600 IOKBS questions were evaluated according to the knowledge dimension of RBT, it was determined that most questions were conceptual (71 questions) in fifth grade, factual (73 questions) in sixth grade, conceptual (65 questions) in seventh grade and conceptual (58 questions) in eighth grade. No question containing metacognitive information could be identified. It has been observed that the accumulation is greater in factual and conceptual knowledge. When the questions were evaluated according to cognitive level, it was determined that the most questions in the fifth grade were from the comprehension level (54 questions), in the sixth grades from the remembering level (68 questions), in the seventh grades from the understanding (55 questions) and remembering levels (55 questions), and in the eighth grades from the comprehension level (54 questions). It has been determined that there is no question in the creation step. It was observed that the number of tests evaluated in the exam measured lower-level questions was higher than the number of measurements in higher-level questions. The study concluded that the science questions in IOKBS consist of a structure that does not prioritize creativity and supports a rote-based thinking style. Science test questions in IOKBS may focus on cognitive domain steps that will reveal higher-level thinking.